MANAJEMEN AGROWISATA JAMBU KRISTAL SEBAGAI IMPLEMENTASI TEORI MODAL SOSIAL JAMES COLEMAN - Sukma, Qorry Aini Zianida; Astutik, Dwi; Siregar, Riadi Syafutra (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2024)
Indonesia has abundant potential resources which are very beneficial for society and can be developed into a tourist destination. One potential area is Tengklik Hamlet, Polokarto Village, Polokarto District, Sukoharjo Regency, Central Java, which operates in the agricultural sector under the name Larasati Garden agrotourism. This research aims to examine James Coleman's social capital theory which can be implemented in the management of Larasati Garden agrotourism. A qualitative approach with a case study type was used in this research. The results obtained are that social capital plays an important role in the success and sustainability of agrotourism management. This social network was formed starting from agrotourism owners who actively built good relationships with the people of Tengklik Hamlet. Applicable social norms include aspects such as work ethics, compliance with rules, and environmentally friendly behavior. Trust built through transparency, open communication and consistency of action is the main foundation in maintaining harmony and success in agrotourism operations. The application of James Coleman's social capital theory has proven to make a significant contribution to the management of Larasati Garden agrotourism. Strong social networks between owners, local communities and visitors facilitate effective collaboration in maintaining operational sustainability and facility development.